2010
DOI: 10.1016/j.nimb.2009.09.046
|View full text |Cite
|
Sign up to set email alerts
|

GISAXS and GIWAXS analysis of amorphous–nanocrystalline silicon thin films

Abstract: Amorphous-nanocrystalline silicon thin films were deposited by Plasma Enhanced Chemical Vapor Deposition (PECVD) on glass substrate with various silicon nanocrystal size distributions and volume fractions. The samples were examined by Grazing Incidence Small Angle X-ray Scattering (GISAXS) and Grazing Incidence Wide Angle X-ray Scattering (GIWAXS) at the Austrian SAXS beamline (Synchrotron Elettra, Trieste) using an X-ray beam energy of 8 keV. The grazing incidence angle varied from the critical angle to 0.2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…S5 and S6). The GIWAXS and GISAXS, in addition to RSoXS measurements were carried out to investigate the effect of BT on morphology of PTB7:PC 71 BM and PBDTTT‐C:PC 71 BM films, and the specimens processed with DIO additive were selected for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S5 and S6). The GIWAXS and GISAXS, in addition to RSoXS measurements were carried out to investigate the effect of BT on morphology of PTB7:PC 71 BM and PBDTTT‐C:PC 71 BM films, and the specimens processed with DIO additive were selected for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that BT additive has no obvious effect on the small PC 71 BM aggregates. Moreover, the peak ranging from 0.43 to 0.48 nm −1 could be roughly calculated ( d = 2normalπq, which d means domain spacing and q means a magnitude of 4π∙sinθ/λ, where λ is the wavelength of incident angle and θ is the half scattering angle), and the average domain size is 13.09–14.61 nm. After illumination for 1 h, the scattering intensity of PBDTTT‐C:PC 71 BM decreases in a monotonic mode, probably due to the low contrast in electron cloud intensity.…”
Section: Resultsmentioning
confidence: 99%
“…B) of the SiNCs film evaluated from the GIWAXS pattern confirms the presence of the SiNCs in the ultrathin films, where the broadening is ascribed to the quantum confinement size of the SiNCs whereby the general expression for the line broadening is given by Williamson and Hall . The characteristic diffraction lines are broadened and their width differs by variation of grazing incidence angle indicating the variation of nanocrystals sizes .…”
Section: Resultsmentioning
confidence: 99%
“…Optical, vibrational, and electrical properties of QDs make them practical for silicon film solar cells. Juraić et al investigated properties of QD, or so‐called nanocrystals, and its surroundings using GISAXS and grazing‐incidence wide‐angle X‐ray scattering (WAXS) at the Austrian beamline of ELETTRA. Nanocrystalline Si, with various QD fractions, was deposited on a glass substrate by plasma‐enhanced chemical vapor deposition.…”
Section: Diffractionmentioning
confidence: 99%